Approaching soft X-ray wavelengths in nanomagnet-based microwave technology - Haiming Yu (Nature Portfolio, 2016)
Integrating spin waves with microwave circuits is promising for microwave nanoelectronics. Here, Yu et al. demonstrate a reconfigurable microwave-to-magnon transducer by covering yttrium iron garnet with small arrays of tailored magnetic nanodisks, which transmits microwave signals via sub-100-nanometer wavelength spin waves.